RETRACTED: Thermoreversible Structurally Recoverable Dual‐Network Elastomer Hydrogel - Kun Lei; Chengyuan Sun; Chongchong Yang; Zhen Zheng; Xinling Wang (Macromolecular Materials and Engineering)
Abstract Comprising a hydrogen bond crosslinked agarose (Aga) network and a covalently crosslinked hydroxyethyl polyacrylate network, a simple, easily controlled one‐pot construction of agarose/hydroxyethyl polyacrylate (Aga/PHEA) double network (DN) elastomer hydrogel is developed. The Aga/PHEA DN gels combining the strengths of both hydrogel and elastomer indicate excellent fatigue resistance, toughness together with rapid, high recoverable rate. The compression strength, tensile strength, and toughness of DN gels can reach 41 MPa, 1.0 MPa, and 6.7 MJ m−3. Due to the thermoreversible feature of agarose, the gel displays an excellent recoverable ability with the elastic modulus recovery of 93% and the energy loss recovery of 90%, respectively, after heating the compressed and released gels. Interestingly, the gels indicate a typical rubber behavior with a small and almost overlapped hysteresis loop and excellent fatigue resistance by simply regulating the content of the second network HEA. Besides, the in vitro MTT and cell adhesion tests confirm the good biological compatibility of the gels. The active hydroxyl groups in the gel can be bonded with functionalized molecule for different needs. The studies reveal that the DN elastomer hydrogels with excellent mechanical properties, biocompatibility, and functionalization will significantly provide a new road to gel researches and applications.